Variability in inclination toward national products among European regions and its impact on consumer behavior - Artamonova, Daria (2021)
The thesis investigates the level of predisposition towards domestic brands in the product category, which is considered "national pride" in three European regions: France, Czech Republic and Russia. The aim of the thesis work was to determine whether there is a notable variability between the levels of this predisposition between European regions and, if these variabilities were found, to determine whether they are related to the overall differences in consumer behavior between regions. It was proved that the level of predisposition is high in all the researched regions and the differences among them are insignificant.